Courses
Courses for Kids
Free study material
Offline Centres
More
Store Icon
Store

If p, q, r denote arbitrary statements, then the logically equivalent of the statement \[p \Rightarrow \left( {q \vee r} \right)\] , is
A. \[\left( {p \vee q} \right) \Rightarrow r\]
B. \[\left( {p \Rightarrow q} \right) \vee \left( {p \Rightarrow r} \right)\]
C. \[\left( {p \Rightarrow \sim q} \right) \wedge \left( {p \Rightarrow r} \right)\]
D. \[\left( {p \Rightarrow q} \right) \wedge \left( {p \Rightarrow \sim r} \right)\]

seo-qna
Last updated date: 25th Apr 2024
Total views: 395.1k
Views today: 7.95k
Answer
VerifiedVerified
395.1k+ views
Hint: In this type of question, we have to check each option and simplify it.
A statement with if p, then q is written as p implies q, denoted by $p \Rightarrow q$.
The conditional statement: if p, then q is logically equivalent to negation p or q, denoted by $\left( { \sim p \vee q} \right)$.
The truth table for if p, then q has to be memorized, given as follows:

pq$p \Rightarrow q$
011
001
111
100


The truth table for $\left( { \sim p \vee q} \right)$

pq$p \Rightarrow q$$\left( { \sim p} \right)$$\left( { \sim p \vee q} \right)$
01111
00111
11101
10000


 Thus, $p \Rightarrow q = \left( { \sim p \vee q} \right)$

Complete step-by-step answer:
Find the logically equivalent statement of the given statement.
Given statement: \[p \Rightarrow \left( {q \vee r} \right)\]
We know, for: $p \Rightarrow q$, its logically equivalent statement: $\left( { \sim p \vee q} \right)$.
Hence, for: \[p \Rightarrow \left( {q \vee r} \right)\] logically equivalent statement: \[ \sim p \vee \left( {q \vee r} \right)\].
Also, $\left( { \sim p \vee q \vee r} \right)$

Simplify option (A).
\[\left( {p \vee q} \right) \Rightarrow r\]
Its logically equivalent statement: \[ \sim \left( {p \vee q} \right) \vee r\]
Also, \[\left( {\left( { \sim p \wedge \sim q} \right) \vee r} \right)\]; this is not equal to the logically equivalent statement in step (1).

Simplify option (B).
\[\left( {p \Rightarrow q} \right) \vee \left( {p \Rightarrow r} \right)\]
Its logically equivalent statement: \[\left( { \sim p \vee q} \right) \vee \left( { \sim p \vee r} \right)\]
Also, \[\left( { \sim p \vee q \vee \sim p \vee r} \right)\]
We know,
 $
  a \vee a = a \\
  \because \sim p \vee \sim p = \sim p \\
 $
This implies, the logically equivalent statement becomes: \[\left( { \sim p \vee q \vee r} \right)\] ; which is equal to the logically equivalent statement in step (1)

Simplify option (C).
\[\left( {p \Rightarrow \sim q} \right) \wedge \left( {p \Rightarrow r} \right)\]
Its logically equivalent statement: \[\left( { \sim p \vee \sim q} \right) \wedge \left( { \sim p \vee r} \right)\]
We know, $a \vee \left( {b \wedge c} \right) = \left( {a \vee b} \right) \wedge \left( {a \vee c} \right)$ i.e. “or” operation is distributed over “and” operation.
Hence, the logically equivalent statement becomes: \[\left( { \sim p \vee \left( { \sim q \wedge r} \right)} \right)\] ; which is not equal to the logically equivalent statement in step (1).

Simplify option (D).
\[\left( {p \Rightarrow q} \right) \wedge \left( {p \Rightarrow \sim r} \right)\]
Its logically equivalent statement: \[\left( { \sim p \vee q} \right) \wedge \left( { \sim p \vee \sim r} \right)\]
We know, $a \vee \left( {b \wedge c} \right) = \left( {a \vee b} \right) \wedge \left( {a \vee c} \right)$ i.e. “or” operation is distributed over “and” operation.
Hence, the logically equivalent statement becomes: \[\left( { \sim p \vee \left( {q \wedge \sim r} \right)} \right)\] ; which is not equal to the logically equivalent statement in step (1).

So, the correct answer is “Option B”.

Note: The “and” operation is can also be distributed over “or” operation i.e. $a \wedge \left( {b \vee c} \right) = \left( {a \wedge b} \right) \vee \left( {a \wedge c} \right)$
Alternate method: We can solve by using the truth table as well.

Draw the truth table for all the conditional statements given in the question as well as options.
Compare whose values are equal to the given statement is equal to the given option.
Here, for reference, the truth table for the only correct option is given.


pqr$\left( {q \vee r} \right)$$p \Rightarrow \left( {q \vee r} \right)$\[p \Rightarrow q\]\[p \Rightarrow r\]\[\left( {p \Rightarrow q} \right) \vee \left( {p \Rightarrow r} \right)\]
00001111
00111111
01011111
01111111
10000000
10111011
11011101
11111111


We see that values of \[p \Rightarrow \left( {q \vee r} \right)\] and \[\left( {p \Rightarrow q} \right) \vee \left( {p \Rightarrow r} \right)\] are equal. Thus, \[\left( {p \Rightarrow q} \right) \vee \left( {p \Rightarrow r} \right)\] is the logically equivalent statement of \[p \Rightarrow \left( {q \vee r} \right)\].